ANALISIS PERBANDINGAN KINERJA KEUANGAN PERBANKAN SYARIAH DENGAN PERBANKAN KONVENSIONAL - Adhim, Fauzan (Al-Infaq: Jurnal Ekonomi Islam, 2011)
In conducting the prediction quality level of financial performance, there is the basic approach is fundamental analysis and technical analysis. This analysis is to determine the company's financial performance by using ratios. To assess the soundness of the banking method is used CAMEL (Capital adequacy, Asset quality, Management, Earning, and Liquidity) which is the standard of Bank Indonesia in assessing the soundness of banks. Problems in this study is how the influence of financial ratios which consists of: CAR, NPL, ROE, ROA, BOPO and LDR of financial performance, both from the conventional banking and Islamic banking.